Combined cellular phenotyping and high-throughput sequencing analysis reveals the symbiotic relationships between different types of macadamia root systems and arbuscular mycorrhizal fungi - Gong, Lidan; Ning, Ya; Chen, Yuchun; He, Xiyong; Wu, Zhonghua; Yue, Hai (Frontiers in Sustainable Food Systems, 2024)
Macadamia nuts, scientifically designated as Macadamia integrifolia, are a highly valuable crop that originated in Australia. This study provides a comprehensive examination of the symbiotic relationships between various macadamia root systems and arbuscular mycorrhizal fungi (AMF). The four principal macadamia-producing regions in Yunnan Province were selected for investigation on the basis of meticulous criteria. To determine the AMF infection rate, the roots were stained. Furthermore, high-throughput sequencing was employed to conduct a comprehensive analysis of the fungal diversity in the rhizosphere soil. The findings were definitive, indicating that both normal and cluster roots are capable of establishing a symbiotic relationship with AMF. Secondary forests exhibited significantly elevated fungal diversity relative to normal roots, while cluster roots demonstrated the lowest diversity and notable regional variation, indicating that the environment exerts a considerable influence on inter-root fungi and AMF. The analysis of the fungal community composition revealed that the predominant groups were Ascomycetes and Basidiomycetes. The FUNGuild function prediction clearly indicated distinct differences in the fungal functions of secondary forests, cluster roots, and normal roots. This study provides a scientific foundation for the sustainable development of macadamia nuts and significantly contributes to a deeper comprehension of the intricate interactions between macadamia and AMF, thereby fostering the long-term stable and healthy growth of the macadamia nut industry.